2019
DOI: 10.1021/acs.iecr.9b05640
|View full text |Cite
|
Sign up to set email alerts
|

Primary Nucleation of Benzoic Acid in Aqueous Ethanol Solution

Abstract: The knowledge of crystallization kinetics, especially crystal nucleation, is crucial for crystallization process design and control. In the present paper, the primary nucleation kinetics of benzoic acid in water−ethanol solution was estimated from induction time measurements, where focused beam reflectance measurement was utilized to detect the onset point of nucleation. As a result, the induction times have been found to decrease with increasing mass fraction of water under the same supersaturation. These dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…40 As described in previous publication, when the water composition in solvent mixture was increased from 0.60 to 0.75, the interfacial energy also increased from 1.83 to 6.46 mJ/m 2 . 25 Thus, the decrease in water composition contributes to the occurrence of primary nucleation, resulting in a wider MSZW. 4a) showed that no significant change of CLDs was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…40 As described in previous publication, when the water composition in solvent mixture was increased from 0.60 to 0.75, the interfacial energy also increased from 1.83 to 6.46 mJ/m 2 . 25 Thus, the decrease in water composition contributes to the occurrence of primary nucleation, resulting in a wider MSZW. 4a) showed that no significant change of CLDs was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Both the probes were inserted into the crystallizer, located 19 mm above the impeller. 21,25 Figure 1 presents a set of typical ATR-FTIR spectra of benzoic acid in ethanol−water solution with different concentrations. It is clear that the peak heights at wavenumbers around 1275 and 1455 cm −1 increase with increasing concentration, where the concentration of the black line is the highest and the purple line corresponds to the lowest concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang experimentally determined the MSZW of adipic acid in different polar solvents and confirmed the link between interfacial energy and the nucleation driving force [14]. Antisolvent crystallization is widely used in crystallization processes, and the effect of mixed solvents on solute nucleation has been reported, but most studies are based on the induction period method [15]. There are a few reports on the nucleation kinetics of mixed-solvent systems using the method of determining MSZW.…”
Section: Introductionmentioning
confidence: 90%
“…In practice, in the presence of foreign particles, the effective interfacial energy (γ het ) can be derived from γ hom for a pure homogeneous process as 31 Furthermore, the radius of critical nuclei ( r het crit ) as well as the number of molecules in them ( n het crit ) are calculated by 33 , 34 The J het can be finally expressed as 29 , 35 Here, m refers to the molecular mass of solute; meanwhile, ρ stands for the number of solute molecules in one volume of nucleating solution.…”
Section: Classical Heterogeneous Nucleation Theory (Chnt)mentioning
confidence: 99%